P-687 Sleep parameters and sleep disorders in male and female subjects presenting idiopathic infertility: the ALIFERT case-control study. (30th June 2022) - Sermondade, N; Dupont, C; Faure, C; Léger, D; Czernichow, S; Lévy, R; Caetano, G
Abstract: Study question: To evaluate the association between sleep parameters, sleep disorders and idiopathic infertility. Summary answer: Some sleep parameters, such as bedtime, sleep latency and chronotypes, might be associated with male and female fertility. What is known already: Some studies suggested that sleep might play an important role in reproductive health. Short sleep duration might interfere with the menstrual cycle, sperm parameters or natural fertility. The biological clock chronotype was found to be associated with fertility, with altered sperm parameters in the "evening" type and more reproductive troubles in the "intermediate" type when compared to the "morning" type. Irregular and night work schedules were also associated with some degree of fertility dysfunction, such as irregular menstrual cycles, a longer time to pregnancy, or male infertility. However, the interrelations between sleep and fertility are not fully elucidated. Study design, size, duration: Fertile and infertile couples were recruited in the ALIFERT cross-sectional case–control multicentric study, between September 2009 and December 2013. The study group consisted of 94 infertile men and 95 infertile women, presenting with a primary idiopathic infertility of more than 12 months. The control group consisted in 85 fertile men and 86 fertile women who had a spontaneously conceived child under 2 years of age with a time to pregnancy less than 12 months. Participants/materials, setting, methods: Male and female participants answered the French version of the Pittsburgh Sleep Quality Index, including questions about sleep timing and duration and symptoms of sleep disorders. Sleep parameters were compared between infertile and fertile participants for each sex, and between partners. The Wilcoxon-Mann-Whitney test was used to compare differences in sleep parameters due to a non-normal distribution, and the Fisher's exact test was used for qualitative variables. Main results and the role of chance: Bedtime was significantly later for infertile compared to fertile male participants (p = 0.03). Infertile female participants had significantly later wake time, greater sleep latency and sleep apnea symptoms compared to fertile female participants (p ≤ 0.02). Fertile participants of both sexes were more frequently moderate morning types compared to infertile participants (p ≤ 0.04). No differences were observed regarding total sleep time, time spent in bed, sleep efficacy, insomnia, hypersomnia, or periodic leg movement symptoms. Infertile couples had more frequently different chronotypes than fertile couples (p = 0.02). Differences in wake time between partners were significantly greater among infertile couples (p < 0.01), but no differences were observed for bedtime, time spent in bed and total sleep time (p ≥ 0.22). Limitations, reasons for caution: Sleep parameters were evaluated based on self-reported questionnaire. Further studies including objective measures of sleep will be needed to allow a more objective determination of sleep parameters. A discussion about mechanistic hypothesis should also be considered to better understand the links between sleep and fertility. Wider implications of the findings: Sleep could be an original and innovative parameter to consider in the reproduction field. Further investigation is needed to elucidate how sleep and reproductive functions are interrelated and how sleep might constitute a useful modifiable target in infertility management. Trial registration number: NCT01093378